Supporting and Assessing Agents - LAUX, VOLKER (Journal of Accounting Research, 2017)
ABSTRACT This manuscript proposes a theory of why and when organizations “support” their employees with resources, time, and freedom beyond what seems economically optimal. The idea is that support plays an information‐generating role in that it renders output more informative about employees' abilities. This effect reduces the need to gather additional information about ability via costly monitoring and commits the firm to make replacement/promotion decisions that are more sensitive to performance. Consequently, support indirectly strengthens employees' career concern incentives and reduces the pressure on costly bonus payments. I apply the model to tech companies, academia, and capital budgeting.